Raymond Williams and the radical project of cultural studies - San Juan, Epifanio Jr (Danyag : Journal of Humanities and Social Sciences, 1996)
By enlanrging the general interpretation of "culture," Raymond Williams pioneered the formation of a new discipline called "cultural studies" which deployed the categories of class, gender, sexuality, place, and ethnicity in a dialectical analysis of experience of collectives in concrete circumstances. Williams rigorously applied the principle of "historical specificity" derived from classical Marxism, refined and enriched with the ideas of Bakhtin/Voloshinov on language and Gramsi on hegemony, to produce a mode of critique called "militant particularism." His theory of culture and cultural change situated in the context of the intellectual tradition ha is responding to its summarized in this paper.